Audiômetro virtual: tecnologia integrada ao ensino - Araújo, Deuzimar Pires de (2021)
Purpose: To elaborate a virtual tool, with didactic purposes, that allows the integration of technology to the teaching of Pure Tone Audiometry (PTA) and speech audiometry. Methods: The Interacoustics AD229b audiometer was used as a physical model to achieve the virtual tool. The Visual Basic 6 programming language was used, so that the colors, characters, and functions were similar to the real audiometer. In addition, the possibility of simulating the patient's response was added, as well as of recording the hearing thresholds in a virtual audiogram. For speech audiometry, the possibility of adjusting the VU meter and recording the number of correct and incorrect answers were implemented. Results: The developed tool was able to reproduce frequencies from 125 Hz to 8000 Hz, in intensities ranging from -10 to 110 dB, being possible to use different stimulus, as well as clinical masking by air and bone conduction. The microphone button can be used to facilitate the teaching of speech audiometry. Conclusion: The virtual version of the audiometer is similar to the model equipment, making the integration of technology into teaching feasible, with exemplify the PTA and speech audiometry.